Development and Validation of Caregiver Social Isolation Scale - Shafiq, Sameera; Anwaar ul Mustafa, Muhammad (Pakistan Armed Forces Medical Journal, 2023)
Objective: To develop an indigenous Caregiver Social Isolation Scale (CSIS) in Urdu for caregivers of mental and physical disorders in Pakistan. Study Design: Mixed method study. Place and Duration of Study: Department of Psychology, University of Gujrat, Pakistan, from Jan to Jun 2021. Methodology: An item pool of 48 was generated based on a thematic analysis of structured interviews with six experts and nine caregivers. The content validity was evaluated by three PhDs in Psychology and two Physicians. The reliability calculated on thirty participants for a tryout was 0.95. Item total correlation of item tool was in the acceptable range. A pilot study was done on three hundred individuals. The value of the KMO was 0.952, which showed the adequacy of the data, with the value of Bartlett’s test significant. No item was deducted. The reliability of 48 items on 300 individuals was 0.976, with two factors. First, for the validity of CSIS, data was collected from 120 individuals with standardized Ryff’s psychological well-being scale, Scale of Social Support and Delong Loneliness Scale. Second, confirmatory factor analysis was conducted on 200 caregivers of children with cleft lip and palate. Results: Exploratory factor analysis yielded two factors, mental agony and lack of social cohesion, with 48 items. Model fit indices of CFA on caregivers...... Conclusion: CSIS is a reliable and valid scale for assessing the social isolation experiences of caregivers of either mental or physical diseases in Urdu. Keywords: Cleft lip, Cleft palate, Caregiver social isolation scale, Exploratory factor analysis.